FUNGSI DAN PENERAPAN TASAWUF DALAM KEHIDUPAN MASYARAKAT MODERN - Sofia Maqom; Siti Rohmah; Ahmad Salafudin; Sobirin (STKIP Subang, 2025)
This study aims to examine the role of the application of Sufism in the lives of today's society, with a focus on its contribution to facing social challenges, mental health, and character building. Through a literature study approach, this study presents various literature, including books, articles, and journals that discuss Sufism and its relevance in the context of modern life. Sufism, which is known for its teachings on inner peace, self-control, and values ​​such as tolerance, compassion, and good deeds, shows great potential in overcoming the moral and social problems of today's society. Practices such as dhikr and meditation have been proven effective in reducing stress, improving mental health, and forming positive character. Moreover, the values ​​of Sufism also offer an approach to easing social conflict and building a peaceful and harmonious society. The results of this study indicate that Sufism not only enriches individual spirituality, but also has a real impact on improving social, mental, and character aspects in the modern era. Therefore, Sufism is seen as an important means to form a more tolerant, noble, and compassionate society. Keywords: Sufism, Society, Modern;